The influence of atmospheric boundary layer turbulence on the design wind loads and cost of heliostats. (1st September 2020) - Emes, Matthew J.; Jafari, Azadeh; Coventry, Joe; Arjomandi, Maziar
Highlights: Design wind loads more sensitive to terrain roughness with increasing heliostat size. Pedestal and torque tube dimensions increase with full-scale ABL turbulence. Foundation pile depth dependent on longitudinal and vertical turbulence components. Relative contribution of structural component costs increases with heliostat size. Total heliostat cost reduced by up to 13% in a low-roughness turbulence field. Abstract: This paper investigated the influence of the turbulent wind fluctuations in the lowest 10 m of the atmospheric boundary layer (ABL), depending on the surface roughness of the terrain surrounding a heliostat field, on the required dimensions and material cost of the structural heliostat components to resist the combined bending and torsional stresses due to the design wind loads. Turbulence data in the lowest 10 m of the full-scale ABL from ESDU 85020 were correlated with peak wind load coefficients on model-scale heliostats in wind tunnel experiments to determine the design wind loads as a function of heliostat size and terrain roughness. The results highlight the large dependence of wind loads and cost on terrain roughness with increasing heliostat size. The increasing mass of steel per unit area in the pedestal, torque tube and support mass led to their relative contribution increasing from 18% of the total specific cost of a 25 m 2 heliostat to 34% of the total cost of a 150 m 2 heliostat. The effect of the increasing turbulence characteristics in a high-roughness terrain resulted in a 10% increase in the total cost of a 25 m 2 heliostat and a 13% increase in the total cost of a 150 m 2 heliostat. An improved understanding of the influence of ABL turbulence on the design wind loads on full-scale heliostats can therefore allow the dimensions of structural components and the respective material cost of manufacturing to be optimised for the local wind conditions and terrain at different sites.